2020
DOI: 10.1177/0967391120913723
|View full text |Cite
|
Sign up to set email alerts
|

Natural fibres as promising environmental-friendly reinforcements for polymer composites

Abstract: Polymer composites are an important class of materials widely being used for many applications. But the main concern of non-degradability and adverse environmental impact of the polymer matrices and the synthetic reinforcements have given forth the need of environmental-friendly polymer matrices and reinforcements used in them. An attempt of such kind is to use the natural plant fibres as the reinforcements that have no harmful impact on the environment and also, they are cost effective. With growing interest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 127 publications
(151 reference statements)
0
17
0
Order By: Relevance
“…Gowda et al [8] worked on various types of natural fibers, i.e., silk, bamboo, kapok, coconut fiber, which were reinforced with polymer matrices and reported that the addition of natural fiber enhances the mechanical and thermal characteristics of the polymer matrices by 6-10%. Similarly, Abdul Karim et al worked on various natural fibers, such as hemp, coir, and jute, and studied the properties of the mechanical and thermal characteristics of hybrid natural polymer composites and enhanced its properties to 4-8% [9]. Sheng and Gimbun found that an increment in the fiber volume fraction increases the flexural strength linearly from 4% to 6% up to 0.4 fiber fraction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Gowda et al [8] worked on various types of natural fibers, i.e., silk, bamboo, kapok, coconut fiber, which were reinforced with polymer matrices and reported that the addition of natural fiber enhances the mechanical and thermal characteristics of the polymer matrices by 6-10%. Similarly, Abdul Karim et al worked on various natural fibers, such as hemp, coir, and jute, and studied the properties of the mechanical and thermal characteristics of hybrid natural polymer composites and enhanced its properties to 4-8% [9]. Sheng and Gimbun found that an increment in the fiber volume fraction increases the flexural strength linearly from 4% to 6% up to 0.4 fiber fraction [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has high stiffness and strength and can protect the cell wall from the outside environment. The amount of lignin in the plant cell wall ranges from 10 to 25% by weight, while the amounts of hemicellulose and cellulose are 20–35% and 35–50%, respectively [ 1 , 10 , 11 ]. The main component of the cell wall is cellulose, composed of repeating units of cellobiose, linked together with β-1,4 linkages, as shown in Figure 1 .…”
Section: Nanocellulose and Its Various Sourcesmentioning
confidence: 99%
“…Polymeric cellulosic materials with high biodegradability and eco-friendliness have received a lot of attention, owing to the damage caused by petroleum base products, such as global warming, green gas emissions, and many others [ 1 ]. Several researchers are working on cellulosic fibers, from which nanocellulose can be extracted.…”
Section: Introductionmentioning
confidence: 99%
“…Hard body armor is typically composed of steel alloys and ceramic composites, whereas soft body armor is predominantly composed of aramid material and natural fibers embedded in a polymer. [57][58][59][60] Personal protection items are in great demand in a variety of activities, and it is a highly competitive market with a high level of interest. Manufacturers and researchers in this industry are working on new materials and methods that can help to improve an individual's safety even further.…”
Section: Introduction To Protection Clothing and Equipmentmentioning
confidence: 99%